Effect of temperature and storage methods on liquid digestate: Focusing on the stability, phytotoxicity, and microbial community. (15th March 2023) - Yan, Jing; Chen, Xiaotian; Wang, Ziyu; Zhang, ChaoJun; Meng, Xingyao; Zhao, Xiaoling; Ma, Xuguang; Zhu, Wanbin; Cui, Zongjun; Yuan, Xufeng
Graphical abstract: Highlights: DOC was the foremost parameter influencing the phytotoxicity of LD. Temperature accelerated the stability and phytotoxicity disappearance of LD. Open storage of LD at 30 °C for 60 days and 20 °C for 90 days of LD was safe. Hermetic storage of LD at 30 °C for 120 days and 20 °C for 150 days of LD was safe. For storage at 10 °C for 180 days, additional post-treatment is required. Abstract: Identifying the stability and phytotoxicity of liquid digestate (LD) is necessary for safe agricultural utilization. Storage temperature, method, and time are critical factors that affect the stability and phytotoxicity of LD. This study therefore aimed to explore the dynamics of stability, phytotoxicity, and microbial community of LD in cattle farms under different storage conditions. The results showed that the contents of solids, organic matter, nitrogen, and phosphorous decreased during storage and exhibited temperature dependency. Conversely, the seed germination index increased, which was negatively correlated with dissolved organic carbon and ammonium nitrogen and positively correlated with certain bacteria ( Thermovirga and Fastidiosipila ). Open storage and/or higher temperature were found to contribute to the stabilization efficiency and phytotoxicity disappearance of LD. Open storage of LD at 30 °C for 60 days and 20 °C for 90 days was safe for its agricultural utilization, while hermetic storage of LD at 30 °C for 120 days and 20 °C for 150 days was safe. However, for storage at 10 °C for 180 days, additional post-treatment is required.